Kepemimpinan Kepala Madrasah dalam Melaksanakan Supervisi Pendidikan Agama Islam - Jabbar, Abdul (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
This article aims to explain the implementation, evaluation, and follow-up on the results of the supervision of the leadership of the Head of Madrasah Diniyyah Ihya Ulumuddin in carrying out supervision. This study uses a descriptive qualitative approach, collecting data using observation, documentation, and interview methods. The results of this study indicate that if the process of implementing the supervision of the Madrasah Head is properly evaluated and the results of the evaluation are followed up properly, then leadership can run well.